Survey on Lending Practices to SMEs in Austria - Lindner, Bernhard (World Bank, Vienna, 2016)
The importance of small and medium enterprises (SMEs) to economic development and job creation is increasingly recognized across the world. With an expected 58 percent of gross value added in 2012, SMEs are perceived to be the backbone of the economy especially within the European Union (EU). Although they faced particularly challenging economic conditions in 2011-12, SMEs within the EU still account for more than 98 percent of all enterprises and 67 percent of total employment. For such businesses, access to finance is a key factor for business start-up, development, survival, and growth. In September-October 2012, the World Bank Centre for financial reporting reform (CFRR) surveyed Austrian banks with a view to understanding the role played by financial information and audits in lending decisions. Respondents to the survey represent approximately one third of the sector based on total assets. The survey also assessed how banks measure the quality of the financial information they receive as part of a loan application. The purpose of this report is to inform the accounting and auditing profession, policy makers, and SMEs and their representative institutions about banks’ requirements and expectations regarding the scope of financial information provided by SMEs when applying for a credit.